Who was impacted and how? The COVID-19 pandemic and the long uneven recovery in India - Mrinalini Jha; Rahul Lahoti (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
We investigate the impact of the COVID-19 pandemic on income levels, poverty, and inequality in both the immediate aftermath and during the uneven recovery until December 2021 using high-frequency household survey data from India. We find that the average household incomes dropped sharply during the months of the nationwide lockdown. The subsequent recovery remained incomplete and was unevenly spread over the population even 22 months after the start of the pandemic. Poverty more than doubled during the lockdown and even after almost two years was slightly higher than before the pandemic. Inequality spiked during the lockdown but returned back to pre-pandemic levels. Using an event study model, we find that the initial shock of the lockdown was more severe for the bottom of the income distribution, but it experienced a faster recovery. On the other hand, the top end of the distribution experienced smaller declines and slower recovery. Levels of formality and contact intensiveness of occupations of people across the distribution help explain this uneven impact and recovery.
Keywords: D6; D63; I3; O15; 330; COVID-19; poverty; inequality; income distribution; India